Optimization method and development with use of ABC program the input dynamical matcher with reduced slope of beam envelope in wide range of beam currents for heavy ion high current RFQ - Vorobyov, I.A. (Вопросы атомной науки и техники, 2006)
An analytical law developed earlier for an output matcher in an initial part of RFQ electrodes was adopted for an input
unmodulated dynamical (radio) matcher (IRM). An analytical formula describing the different types of matchers
was proposed. The modernization of the code ABC was carried out for channel optimization by applying the analytical
formulae. Developed was the method for matchers’ optimization with maintenance of beam dynamical matching in the
wide range of currents and low sensitivity to the initial RFQ segment with a fringe field difficult to control. Раніше розроблений аналітичний закон для вихідного узгоджувача початкової частини ПОКФ
адаптовано для вхідного немодульованого динамічного узгоджувача. Запропоновано аналітичну формулу,
що описує різні типи узгоджувачів. Виконано модернізацію програми АВС для оптимізації каналів із
застосуванням аналітичних формул. Розроблено метод оптимізації узгоджувачів із збереженням
динамічного узгодження в широкому діапазоні струмів і зниженою чутливістю до початкової ділянки
ПОКФ з важко контрольованим спадом крайового поля. Ранее разработанный аналитический закон для выходного согласователя начальной части ПОКФ адаптирован для входного немодулированного динамического согласователя. Предложена аналитическая формула, описывающая различные типы согласователей. Выполнена модернизация программы АВС для оптимизации каналов с применением аналитических формул. Разработан метод оптимизации согласователей с сохранением динамического согласования в широком диапазоне токов и сниженной чувствительностью к начальному участку ПОКФ с трудно контролируемым спадом краевого поля.